Assessment Of Bacteriological quality Of Raw Milk In Trichur And Its Public Health Importance - Anju Raghunathrao Kapre (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 1995)
In the present study an effort has been made to assess the bacteriological quality of raw milk obtained from three different sources in Trichur. A total of 21 individual and seven pooled samples were collected from each sources (S1, S2 and S3), over a period of five months. The samples were subjected to different bacterial counts and also for the isolation and identification of S. aureus and E. coli. The isolates were tested for their sensitivity to various chemotherapeutic agents. The average total viable count of individual milk samples from S1, S2 and S3 were 7.5 x 104, 1.4 x 105 and 2 x 105 CFU per ml respectively. Significant difference (P < 0.01) between the counts from S1 and S2; and S1 and S3 was noticed. The average coliform count for S1 was 2.4 x 10, for S2 was 4.8 x 104 and for S3 was 3.8 x 103 CFU per ml. There was significant difference (P < 0.01) between the counts from S1 and S2 ; S1 and S3 ; and S2 and S3. The average counts for thermotolerant coliforms in samples from S1, S2 and S3 were 2.2 x 10, 2.4 x 104 and 2.4 x 103 CFU per ml. The counts from S1 and S2 ; and S1 and S3 differed significantly (P < 0.01). The average faecal streptococcal counts for the sample from S1, S2 and S3 were 1.5 x 102 , 2.1 x 103 and 1.7 x 103 CFU per ml. Significant difference (P < 0.01) between the counts from S1 and S2 , and S1 and S3 was noticed. The staphylococcal counts in samples from S1, S2 and S3 averaged 5.7 x 102, 2.8 x 103 and 6.8 x 103 CFU per ml respectively. Significant differences (P < 0.01) between the counts from S1 and S2 , and S1 and S3 were noticed. The average S. aureus count in samples from S1 was 8.5 x 10, from S2 it was 1.8 x 102 and from S3 , 7.1 x 10 CFU per ml. The average E. coli counts in samples from S1, S2 and S3 were 2 x 102, 1.2 x 104 and 1.5 x 103 CFU per ml respectively. The counts in samples from S1 and S2 ; S1 and S3 ; and S2 and S3 differed significantly (P < 0.01). The average total viable count in pooled milk samples from S1 , S2 and S3 were 4 x 104 , 1.8 x 106 and 2.1 x 105 CFU per ml respectively. Significant difference (P < 0.01) between the counts from S1 and S2 and S1 and S3 was noticed. The average coliform counts at 370C of incubation in the pooled samples from S1, S2 and S3 were 5.5 x 10, 2 x 105 and 6.4 x 103 CFU per ml respectively. The counts from S1 and S2, S1 and S3 ; and S2 and S3 were found significantly different (P < 0.01). The average thermotolerent count in samples from S1, S2 and S3 were 2.8 x 10, 3.6 x 104 and 4.4 x 103 CFU per ml respectively. Significant difference (P < 0.01) in the counts of S1 and S2 ; and S1 and S3 was noticed. The average faecal streptococcal count in samples from S1, S2 and S3 were 2 x 102, 4.8 x 103 and 2.9 x 103 CFU per ml respectively. Significantly different (P < 0.01) counts were noticed between S1 and S2 ; and S1 and S3 was noticed. The average staphylococcal count in samples from S1 was 9.2 x 102 from S2 was 5.3 x 104 and from S3 was 1.3 x 104 CFU per ml. The counts in samples from S1 and S2 ; and S1 and S3 were significantly different (P < 0.01). The S. aureus counts in milk samples from S1, S2 and S3 averaged 1 x 102, 4.8 x 102 and 1.1 x 102 CFU per ml respectively. The average E. coli count in samples from S1, S2 and S3 were 2.7 x 102, 8.9 x 104 and 1.9 x 103 CFU per ml respectively. Significant difference (P < 0.01) between the counts of samples from S1 and S2 ; S1 and S3 ; and S2 and S3 was observed. All the individual samples from S1 were either of very good or good grades (95.24 and 4.76%) respectively. All the pooled milk samples from this source was of very good grade. Most of the individual samples from S2 were of very good or good grades ( 76.20 and 23.80%) respectively, but the pooled milk samples from S2 were of very good, good, fair and poor grades (42.84, 28.60, 14.28 and 14.28%) respectively. Among the individual samples from S3 source all were of either very good or good grades (80.95 and 19.05%) respectively. Pooled milk samples from the same source had very good and good grade (57.14 and 42.86%) respectively. None of the samples from this source were of fair or poor grades. Of the 60 suspected colonies isolated, 54 were identified as S. aureus. Antibiogram of S. aureus isolates showed highest sensitivity to cloxacillin (100%) and gentamicin (100%) followed by amoxicillin (87.03%), chloramphenicol (77.80%) and penicillin – G (35.20%). Of the 70 suspected colonies isolated 66 were identified as E. coli. The E. Coli. Isolates were most sensitive to gentamicin (96.96%) followed by amplicillin (93.92%), furazolidone (80.30%) and carbenicillin (15.155). Doxycycline was least effective drug with no sensitivity and high resistance (90.90%).